Identification of insertion sites for the integrative and conjugative element Tn916 in the Bacillus subtilis chromosome - Emily L. Bean; Janet L. Smith; Alan D. Grossman (PLoS ONE, 2025)
Integrative and conjugative elements (ICEs) are found in many bacterial species and are mediators of horizontal gene transfer. Tn 916 is an ICE found in several Gram-positive genera, including Enterococcus , Staphylococcus , Streptococcus , and Clostridioides (previously Clostridium ). In contrast to the many ICEs that preferentially integrate into a single site, Tn 916 can integrate into many sites in the host chromosome. The consensus integration motif for Tn 916 , based on analyses of approximately 200 independent insertions, is an approximately 16 bp AT-rich sequence. Here, we describe the identification and mapping of approximately 10 5 independent Tn 916 insertions in the Bacillus subtilis chromosome. The insertions were distributed between 1,554 chromosomal sites, and approximately 99% of the insertions were in 303 sites and 65% were in only ten sites. One region, between ykuC and ykyB ( kre ), was a ‘hotspot’ for integration with ~22% of the insertions in that single location. In almost all of the top 99% of sites, Tn 916 was found with similar frequencies in both orientations relative to the chromosome and relative to the direction of transcription, with a few notable exceptions. Using the sequences of all insertion regions, we determined a consensus motif which is similar to that previously identified for C. difficile . The insertion sites are largely AT-rich, and some sites overlap with regions bound by the nucleoid-associated protein Rok, a functional analog of H-NS of Gram-negative bacteria. Rok functions as a negative regulator of at least some horizontally acquired genes. We found that the presence or absence of Rok had little or no effect on insertion site specificity of Tn 916 .